2005
DOI: 10.1093/brain/awh503
|View full text |Cite
|
Sign up to set email alerts
|

Mutant SOD1 alters the motor neuronal transcriptome: implications for familial ALS

Abstract: Familial amyotrophic lateral sclerosis (FALS) is caused, in 20% of cases, by mutations in the Cu/Zn superoxide dismutase gene (SOD1). Although motor neuron injury occurs through a toxic gain of function, the precise mechanism(s) remains unclear. Using an established NSC34 cellular model for SOD1-associated FALS, we investigated the effects of mutant SOD1 specifically in cells modelling the vulnerable cell population, the motor neurons, without contamination from non-neuronal cells present in CNS. Using gene ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
124
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 175 publications
(134 citation statements)
references
References 57 publications
9
124
0
1
Order By: Relevance
“…A similar reduction in Nrf2 expression was previously observed in a motor neuron-like NSC34 cell line transfected with a mutant SOD1 expression vector and in motor neurons from SOD1-associated familial ALS cases (Kirby et al, 2005). This reduction in Nrf2 expression could explain the increased susceptibility of SOD1 G93A motor neurons not only to NGF but also to Fasmediated apoptosis, which also involves ROS and RNS production (Raoul et al, 2002).…”
Section: Reexpression Of P75supporting
confidence: 69%
“…A similar reduction in Nrf2 expression was previously observed in a motor neuron-like NSC34 cell line transfected with a mutant SOD1 expression vector and in motor neurons from SOD1-associated familial ALS cases (Kirby et al, 2005). This reduction in Nrf2 expression could explain the increased susceptibility of SOD1 G93A motor neurons not only to NGF but also to Fasmediated apoptosis, which also involves ROS and RNS production (Raoul et al, 2002).…”
Section: Reexpression Of P75supporting
confidence: 69%
“…Gene expression profiling of the widely used NSC34 cellular model of SOD1-related FALS identified a marked degree of transcriptional repression in the presence of the SOD1 G93A mutation (Kirby et al 2005). These repressed genes included a group of antioxidant response (ARE) genes or "programmed cell life" genes that are regulated by the Nrf2 transcription factor (Figure 1).…”
Section: Results From Use Of Cellular Models Of Alsmentioning
confidence: 99%
“…Pathologically, it is characterized by progressive, selective motor neuron loss in the brain and spinal cord [2,3] . Mutations in copper/zinc superoxide dismutase (SOD1) account for ~20% of familial cases of ALS [3,4] . In this study, mice overexpressing the G93A mutation of SOD1 were used to model ALS.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study and those of others have shown the accumulation of autophagic vacuoles in the spinal cord of SOD1 G93A mice and ALS patients, suggesting a role of autophagy in the pathogenesis of ALS [5,10] . We further reported that targeting autophagy with rapamycin, a classic autophagy activator, significantly exacerbates motor neuron loss and fails to Neurosci Bull August 1, 2015, 31 (4): [459][460][461][462][463][464][465][466][467][468] 460 remove the abnormal mutant SOD1 aggregates, raising the possibility of autophagic flux defects in SOD1 G93A mice [11] .…”
Section: Introductionmentioning
confidence: 99%